The effect of ZnO 虠 Ta2O5 substitution on the structural and thermal properties of SiO2-ZnO-SrO-CaO-P2O5 glasses - Alhalawani, A.M.F.; Towler, M.R. (Elsevier, 2016)
A series of glasses based on the system 48SiO2-(36-X) ZnO-6CaO-8SrO-2P2O5-XTa2O5 with X varying from 0 mol% (Ta0) to 8 mol% (Ta4) were fabricated. The structural features as a function of Ta2O5 content were investigated by network connectivity (NC) calculations, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR). The thermal properties of the glasses were obtained by performing simultaneous thermal analysis (STA). XRD showed that all compositions were predominantly amorphous, however the incorporation of tantalum pentoxide (Ta2O5) resulted in a small degree of crystallinity within the sample. Replacing ZnO with Ta2O5 increases the glass transition, crystallization and melting temperatures. Further, Ta2O5 incorporation results in higher thermal stability suggesting a greater glass forming tendency and the insertion of Ta in the glass network. XPS and FTIR spectroscopy revealed that Ta behaves as a glass former and that Zn has an intermediary role in the vitreous network.